Desafios da gestão de frotas de uma instituição púbica do Estado de Minas Gerais - Ferreira, Michelle Borges de Noronha (2024)
This research work aims to investigate the challenges of fleet management in a public sector organization. For this purpose, the research object chosen was the direct administration body of the State of Minas Gerais that has the largest fleet, with approximately 9,327 vehicles. The study started with the following question: how can a public organization, whose main activity is linked to the use of vehicles, increase its effectiveness through efficient fleet management? The bibliographic research that supported the theoretical framework presents innovation in public sector operations management, with a focus on fleet management. Through documentary research and secondary data, a timeline of the evolution of the fleet management process in the organization is created. The results indicate that fleet management is a priority in the corporation’s strategic planning, demonstrating a continuous effort to increase the effectiveness of fleet use, either through the incorporation of emerging technologies or the adoption of new management models. Currently, the organization is in the process of implementing the Vehicle Telemetry Monitoring System, a technology that goes beyond simple vehicle tracking. It allows efficient monitoring and control in various areas, with real-time data collection, enabling process optimization, cost reduction, increased employee safety, and consequently, increased public service effectiveness, which is the main objective of the public sector. The academic contributions demonstrate the effort to update public institutions in response to public governance and innovation demands. The study’s limitations reflect the restrictions imposed by the data collection method. As a technological product, a Executive Sumary with suggestions for the implementation of the Telemetry System in the institution is presented.